METHODOLOGICAL BASIS FOR THE DEVELOPMENT OF INTERNAL QUALITY ASSURANCE SYSTEM IN MILITARY HIGHER EDUCATIONAL INSTITUTIONS - Kravets, Valentyna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . Recently approved by the Cabinet of Ministers of Ukraine Concept of the military education system transformation defines ensuring the quality of military education taking into account NATO standards as one of the urgent tasks. Today, not all military higher educational institutions of Ukraine completed the institutionalization of the internal quality assurance system, the mandatory implementation of which is established by the Ukrainian legislation. This process requires further improvement and methodological support. Therefore, the methodological basis of the development of the internal quality assurance system at the military HEIs need for research. The purpose of the study is to determine the methodological basis for the development of an internal quality assurance system at the Ukrainian military HEIs, taking into account the up-to-date experience of domestic higher education institutions and NATO quality standards. M e t h o d s . Theoretical analysis of scientific publications on the issues under study; statistical data analysis on the ISO 9001 standard implementation in Ukraine; comparative analysis of the laws of Ukraine, regulatory documents of the European Higher Education Area, NATO and higher education institutions on quality assurance issues; generalization and synthesis. R e s u l t s . The methodological concepts for the development of an internal quality assurance system in educational organizations are characterized: ESG-2015, ISO 9001, the EFQM excellence model. It is substantiated that the most acceptable methodological concept for the development of such a system at military HEIs are the ESG-2015 internal quality assurance standards and the NATO quality management system standards. On the basis of comparative analysis of these standards, as well as the requirements of the laws of Ukraine on the education quality, a list of the internal quality assurance procedures for the military HEIs is proposed. The levels of the structural model of the internal quality assurance system for military HEIs have been clarified. C o n c l u s i o n s . It has been established that the structure of the internal quality assurance system for military HEIs does not fundamentally differ from the model of such a system for any HEI in Ukraine except the procedure of contributing to NATO. But the implementation of the procedures related to ensuring student-centeredness and publicity in military HEIs, has features that require further research.